Pendidikan Multikultural dalam Mendukung Penguatan Moderasi Beragama : Tinjauan Historis - Topan, Ali; A. Fatikhul Amin Abdullah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
In the course of history after the New Order, conflicts between religious communities often occurred, but in Pamekasan itself, including part of Madura, there has never been a conflict between religious people, all hudup are harmonious and tolerant. Therefore, this study analyzes multicultural education in supporting the strengthening of religious moderation in Avalokitesvara Pamekasan Temple using historical methods, The first is the process of collecting sources, primary sources are in the form of interviews with the head of the monastery, teachers and people considered important in this research, archives and observations of researchers, while secondary sources are obtained from books, scientific articles, and proceedings. Second, source criticism with internal and external criticism. The third step is interpretation and the last is historiography. Structural Functionalism theory approach from Talcott Parsons. The results of the study show that multicultural education is effective in supporting the strengthening of religious moderation for students at Avalokitesvara Temple, because students can see firsthand the diversity in the Temple. Multicultural education produces an understanding of religious moderation, and religious moderation produces an attitude of tolerance, inclusiveness, harmony and respect for differences, so as to create harmony between religious communities in the Land of Salam Gate (Pamekasan).